The European Stability Mechanism: Bastion of calm or crisis accelerant? - Alexandra M. D. Hild; Bernhard Herz; Christian Bauer (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
The European Stability Mechanism (ESM) is the permanent crisis resolution mechanism for euro area countries. We analyze the costs of the current (suboptimal) refinancing design of the ESM and evaluate an alternative asset-backed securities (ABS) structure under different scenarios. Our simulation results indicate that switching to an ABS structure could substantially lower ESM refunding costs by up to 3.5%. Moreover, the current structure severely limits the ESM's potential to stabilize financial markets. In particular, in the most likely type of future crises, namely medium-sized requests for financial support from distressed ESM members accompanied by other ESM countries unwilling or unable to provide new capital, the ESM is likely to unintentionally act as a crisis accelerant rather than a stabilizer.
Keywords: E6; F34; F55; G15; 330; European Stability Mechanism (ESM); financial instruments; euro area; ABS